Synthesis of Biokerosene through Electrochemical Hydrogenation of Terpene Hydrocarbons from Turpentine Oil - Tedi Hudaya; Ongky Widjaja; Antonius Rionardi; Tatang Hernas Soerawidjaja (Journal of Engineering and Technological Sciences, 2016)
Indonesia possesses great potential for developing renewable resources as alternative fuels. For example, turpentine oil obtained from Pinus merkusii, which contains mostly monoterpene hydrocarbons (C10H16). The oil is highly suitable to be processed for biokerosene or even jet biofuel. It consists of hydrocarbons within the range of C10 to C15. However, it contains insufficient H and thus needs to be upgraded. In the present work, electrochemical hydrogenation was used for upgrading. In the electrochemical cell, stainless steel, silver, and carbon were used alternately for the anode, while copper and silver Raschig rings were used for the cathode. An electrolyte solution of cuprous ammonium formate was utilized not only as a source of H but also to draw the unsaturated hydrocarbons into the aqueous phase. The electrolyte : oil ratio (up to 2:1), electrolyte concentration (between 0.4 and 2 M) and reaction time were varied throughout the experiments. The bromine number (unsaturation level) of the turpentine oil, which was initially 1,86 (mole Br2/mole), was lowered significantly to 0.69-0.90. Promising increase of smoke point values were observed from 11 mm to 16-24 mm, indicating a higher H content of the processed oil, thus making it suitable as a substitute for petroleum kerosene.